Case report of a behavioral intervention for adherence to haircuts in children with Autism Spectrum Disorder (Research, Society and Development, 2024)
People with Autism Spectrum Disorder (ASD) present inappropriate behaviors in greater prevalence than general population. Such behaviors often show up in several settings, including during the health and personal hygiene routines. This report, that covers a number of cases, aims to present the outcome of an intervention that had, as its purpose, increasing the tolerance of two children diagnosed with ASD to having a haircut. For that, systematic desensitization and differential reinforcement procedures were used. The intervention adopted was effective in establishing an adherence behavior towards the haircut in both participants. The report contributes to the literature regarding the transposition of outcomes derived from applied research to service provision in Applied Behavior Analysis for Autism when it comes to the use of less invasive procedures to increase adherence to daily personal hygiene activities.